(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2025)
Book review: Angele Alook, Emily Eaton, David Gray-Donald, Joël Laforest, Crystal Lameman and Bronwen Tucker. The End of This World: Climate Justice in So-Called Canada. 2023. Toronto. Between the Lines. 219 pages. 29.95 (paperback), ISBN 9781771136129.